Best Answer

Subtracting a negative number is the same as adding the corresponding positive number:

6 - (-3) = 6 + 3

Subtracting a negative number is the same as adding the corresponding positive number:

6 - (-3) = 6 + 3

Subtracting a negative number is the same as adding the corresponding positive number:

6 - (-3) = 6 + 3

Subtracting a negative number is the same as adding the corresponding positive number:

6 - (-3) = 6 + 3

Study guides

☆☆

More answers

Subtracting a negative number is the same as adding the corresponding positive number:

6 - (-3) = 6 + 3

Q: What is positive 6 minus negative 3 equal?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

Positive 3 plus negative 5 minus negative 2 minus positive 4 is equal to -4.

It depends. (a) a positive minus a smaller positive is positive, (b) a positive minus a positive of the same size is zero, and (c) a positive minus a bigger positive is negative. For example, (a) 8 - 6 = 2 (b) 8 - 8 = 0 (c) 8 - 11 = -3

negative 20

3 minus -9 is 12.

negative 5

Related questions

Positive 3 plus negative 5 minus negative 2 minus positive 4 is equal to -4.

8 minus negative three or 8--3 equal positive 11. The double negative converts the minus sign into a plus sign and the negative into a positive.

zero.

3 minus -6 is 9.

-3 - (-2) = -3 + (+2) = -3 + 2 = -1

No, 12/-4 = -3 A negative times negative is positive, so positive divided by negative is a negative.

Negative plus a negative is a negative. Ex. -1+-1=-2 Negative times a negative is a positive. -2*-2=4 But a negative [minus] plus a positive [plus] can be minus, zero or plus: For example, -3 + 2 = -1 -3 + 3 = 0 -3 + 4 = +1

The result can be either positive or negative, depending on the sizes of those original two negative numbers. (-8) minus (-10) = positive 2 (-8) minus (-5) = negative 3

It depends. (a) a positive minus a smaller positive is positive, (b) a positive minus a positive of the same size is zero, and (c) a positive minus a bigger positive is negative. For example, (a) 8 - 6 = 2 (b) 8 - 8 = 0 (c) 8 - 11 = -3

Q) -3-(+7)=-3-7 =-10

-12 - (-3) Two negatives equal a positive. So, -12 + 3 = -9

Not necessarily; it can be negative, zero, or positive. (-5) - (-3) = -5 + 3 = -2 (-5) - (-5) = -5 + 5 = 0 (-5) - (-8) = -5 + 8 = +3